Representation of Women in the Parliament of the Weimar Republic: Evidence from Roll Call Votes. Issue 3 (8th August 2014) - Debus, Marc; Hansen, Martin Ejnar
Abstract : In modern democracies, the representation of voter interests and preferences is primarily the job of political parties and their elected officials. These patterns can, however, change when the issues that are at stake concern the interests of social groups represented by all relevant parties of a political system. In this article we focus on the behavior of female MPs in the parliament of Weimar Germany and, thus, on a parliament where legislative party discipline was very high. On the basis of a dataset containing information on the legislative voting behavior of MPs, we show that gender, even when controlling for a battery of further theoretically derived explanatory factors, had a decisive impact on the MPs' voting behavior on a law proposal to curb the spread of sexually transmitted diseases.